Gene Expression Profiling of IL-17A-Treated Synovial Fibroblasts from the Human Temporomandibular Joint. (29th December 2015) - Hattori, Toshio; Ogura, Naomi; Akutsu, Miwa; Kawashima, Mutsumi; Watanabe, Suguru; Ito, Ko; Kondoh, Toshirou
Abstract : Synovial fibroblasts contribute to the inflammatory temporomandibular joint under pathogenic stimuli. Synovial fibroblasts and T cells participate in the perpetuation of joint inflammation in a mutual activation feedback, via secretion of cytokines and chemokines that stimulate each other. IL-17 is an inflammatory cytokine produced primarily by Th17 cells which plays critical role in the pathogenesis of numerous autoimmune and inflammatory diseases. Here, we investigated the roles of IL-17A in temporomandibular joint disorders (TMD) using genome-wide analysis of synovial fibroblasts isolated from patients with TMD. IL-17 receptors were expressed in synovial fibroblasts as assessed using real-time PCR. Microarray analysis indicated that IL-17A treatment of synovial fibroblasts upregulated the expression of IL-6 and chemokines. Real-time PCR analysis showed that the gene expression of IL-6, CXCL1, IL-8, and CCL20 was significantly higher in IL-17A-treated synovial fibroblasts compared to nontreated controls. IL-6 protein production was increased by IL-17A in a time- and a dose-dependent manner. Additionally, IL-17A simulated IL-6 protein production in synovial fibroblasts samples isolated from three patients. Furthermore, signal inhibitor experiments indicated that IL-17-mediated induction of IL-6 was transduced via activation of NF κ B and phosphatidylinositol 3-kinase/Akt. These results suggest that IL-17A is associated with the inflammatory progression of TMD.